Implementasi Good Governance terhadap Kinerja BPJS Ketenagakerjaan Cabang Meulaboh - Ervira Julia Putri; Alfian Anas (Universitas Teuku Umar, 2023)
The purpose of this study is to examine the implementation of good governance guidelines of BPJS Ketenagakerjaan year 2015 and the BPJS Ketenagakerjaan Regulation Number 2-year 2021 concerning Sharia Services for the Employment Social Security Program in Aceh Province, given that financial institutions operating in Aceh Province are required to comply with sharia principles as regulated in Aceh province as stated in Qanun Number 11-year 2018 concerning Sharia Financial Institutions. This study applied qualitative methods using thematic analysis tools. Interviews were employed as the method of data gathering. The participants in this study were selected using a method of purposive sampling. This study revealed that the application of good governance influences the performance of BPJS Ketenagakerjaan in the Meulaboh branch.